Interannual and decadal variability of the North Equatorial Undercurrents in an eddy-resolving ocean model. Issue 1 (December 2018) - Li, Yiwen; Liu, Hailong; Lin, Pengfei
Abstract In the present study, the mean states of the North Equatorial Undercurrents (NEUCs) simulated in an eddy-resolving ocean model are evaluated, and the variability of the three NEUC jets is analyzed. This analysis provides a reference for future observations regarding how long thein-situ observations should be conducted to obtain a complete picture of NEUCs. We show that the primary features of the three eastward NEUC jets are fairly well reproduced by the high-resolution model of LICOM, such as the locations, tilting directions and widths of the three jets. However, the simulated NEUCs have slightly weaker magnitude and are located at shallower depths. In addition, two dominant time scales on interannual (2–7 years) and decadal (12–19 years) time scales for all three NEUC jets are found in a 39-year high-resolution LICOM simulation, although the latter is not statistically significant. The variation of these jets is related to the remarkable interannual and decadal variability in the Pacific Ocean. Our decomposition analysis indicates that both the small- and large-scale currents contribute to the total variation. Furthermore, the low-pass temporal filter of zonal velocity shows that the quasi-steady cross-basin NEUC jets can only emerge on time scales longer than the interannual periodicity.